General description of the Gödöllő hillside - Demény, Krisztina (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The Gödöllő Hillside, near the capital of Hungary, is rich both in natural and landscape values. Some parts of the region have belonged to a landscape protection area since 1990. Thanks to the characteristics of the relief, this area accounts for a transitory region between a plain terrain and that of mountain ranges of medium heights due to geological, climatic, botanical, and soil features. Its diversity is present not only in physical but also in cultural geography since this area used to be one of Hungary’s most densely covered woodlands, a royal pasture and a hunting area. The landscape of Hungary has changed radically in the past decades. As a result of increasing need for land (spreading of residential areas, greenfield investments etc.) the natural environment has been diminishing. On the other hand, the need of society for intact areas has increased, too. The Gödöllő Hillside bears big environmental stress because it is situated close to the Budapest agglomeration. In the recent years, the effects of suburbanisation manifest more significantly since the population has already started moving out of the capital city. The need for establishing new residential areas grew while cultivated lands are shrinking. Due to land use changes (new roads, houses, less agriculture and sylviculture) the spatial structure becomes more and more fragmented.
Keywords: Gödöllő Hillside; physical geography; natural monuments; landscape elements; cultural monuments